Case Report: Langerhans Cell Sarcoma With Intracranial and Extracranial Communication on the Left Frontal Bone - Xie, Shan; Shao, Zhilin; Shao, Dongqi; Du, Bang; Han, Yi; Li, Yu; Zhang, Binbin; Zheng, Xialin; Jiang, Zhiquan (Frontiers in Surgery, 2022)
Background Langerhans cell sarcoma (LCS) is an extremely rare type of malignant tumor that originates from Langerhans cells (LC). It is characterized by the malignant proliferation and dissemination of LC and is extremely invasive, with rapid progression and a poor prognosis. Treatment includes resection of lesions, radiotherapy, chemotherapy, immunotherapy, and transplantation of hematopoietic stem cells. However, a unified and optimized treatment plan is lacking, and individualized treatment is accepted. Case presentation We report an 18-year-old man with intracranial and extracranial communicative LCS that occurred in only the left forehead without metastasis to other regions. Clinical and hematological data were normal. We undertook complete resection of diseased tissue, which was pathologically examined. Staining (hematoxylin and eosin) showed positivity for cluster of differentiation (CD)1a (++), S-100 protein (++), P53 (++), CD68 (+), cyclin D1 (+), cyclin A (+), cyclin B1 (+), IGF2BP3 (+), and Ki-67 (45%–50%). Recurrence or metastasis were not observed after long-term follow-up. Conclusion LCS is a rare malignant tumor, and one that occurs with intracranial and extracranial communication is even rarer. Active adoption of an individualized treatment plan is crucial.